2012
DOI: 10.1155/2012/254791
|View full text |Cite
|
Sign up to set email alerts
|

Subring Depth, Frobenius Extensions, and Towers

Abstract: The minimum depthd(B,A)of a subringB⊆Aintroduced in the work of Boltje, Danz and Külshammer (2011) is studied and compared with the tower depth of a Frobenius extension. We show thatd(B,A)< ∞ ifAis a finite-dimensional algebra andBehas finite representation type. Some conditions in terms of depth and QF property are given that ensure that the modular function of a Hopf algebra restricts to the modular function of a Hopf subalgebra. IfA⊇Bis a QF extension, minimum left and right even subring depths are shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…In this section, we define depth of algebras and coalgebras in tensor categories. When applied to algebras and coalgebras in a bimodule tensor category, this definition recovers minimum odd depth defined in [7] and h-depth defined in [30]. In particular, a coalgebra in bimodule tensor category is a coring, with depth defined in [16].…”
Section: Depth Of Algebras and Coalgebras In Tensor Categoriesmentioning
confidence: 88%
“…In this section, we define depth of algebras and coalgebras in tensor categories. When applied to algebras and coalgebras in a bimodule tensor category, this definition recovers minimum odd depth defined in [7] and h-depth defined in [30]. In particular, a coalgebra in bimodule tensor category is a coring, with depth defined in [16].…”
Section: Depth Of Algebras and Coalgebras In Tensor Categoriesmentioning
confidence: 88%
“…(1) for some n ∈ N [25]. This in turn is equivalent to there being f i ∈ Hom( B A B , B B B ) and r i ∈ A B such that id A = i f i (−)r i , the classical central projectivity condition [32].…”
Section: 2mentioning
confidence: 99%
“…for some positive integer q[4,24,25]. Note that if B ⊆ A has H-depth 2n − 1, the subalgebra has (left or right) depth 2n by restriction of modules.…”
mentioning
confidence: 99%
“…Proof. The hypothesis of surjectivity is equivalent to: A B (or B A) is a generator [34,Lemma 4.1]. We have elaborated on Miyashita's theory of Morita equivalence of ring extensions in [36,Section 5], where it is shown that Frobenius extension is an invariant notion of this equivalence.…”
Section: Core Hopf Ideals Of Hopf Subalgebrasmentioning
confidence: 99%
“…Remark 4.10. The viewpoint of interior algebras and induced algebra of Puig and [13] is related to the approach of the endomorphism ring tower of a Frobenius extension A ⊆ B with Frobenius homomorphism E : A → B and dual bases tensor [34,Section 4.1] for a complete set of tower equations). Then (*)…”
Section: Core Hopf Ideals Of Hopf Subalgebrasmentioning
confidence: 99%